2019
DOI: 10.1016/j.pld.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevational changes in vascular plants richness, diversity, and distribution pattern in Abune Yosef mountain range, Northern Ethiopia

Abstract: The aim of this research is to investigate the patterns of vascular plant species richness, diversity, and distribution along an elevation gradient in the Abune Yosef mountain range, Ethiopia. Preferential systematic sampling was employed to collect vegetation and environmental data along the elevation gradient. We found that plant species richness declines monotonically from low to high elevations. Specifically, vascular plant species richness and diversity were lower in the Afroalpine grassland (high elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 40 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…Patterns of species community are associated with environmental factors including climate, topography, and soil as well as anthropogenic and livestock disturbances (Whittaker et al 2003). Ecological studies conducted in Ethiopia by Woldu et al (1989), Friis (1992), Bekele (1994), Aynekulu (2011), Kelbessa and Girma (2011) and Gebrehiwot et al (2019) reported the importance of environmental variables (altitude, slope, landscape, disturbances, and soil physical and chemical properties) in shaping plant communities. CCA analysis result showed that environmental variables including altitude, slope, silt, sand, soil organic matter, total nitrogen, and disturbances are associated with species compositions of plant communities in the Hirmi woodland.…”
Section: Floristic Composition and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of species community are associated with environmental factors including climate, topography, and soil as well as anthropogenic and livestock disturbances (Whittaker et al 2003). Ecological studies conducted in Ethiopia by Woldu et al (1989), Friis (1992), Bekele (1994), Aynekulu (2011), Kelbessa and Girma (2011) and Gebrehiwot et al (2019) reported the importance of environmental variables (altitude, slope, landscape, disturbances, and soil physical and chemical properties) in shaping plant communities. CCA analysis result showed that environmental variables including altitude, slope, silt, sand, soil organic matter, total nitrogen, and disturbances are associated with species compositions of plant communities in the Hirmi woodland.…”
Section: Floristic Composition and Diversitymentioning
confidence: 99%
“…This community was less disturbed and had high species richness due to the fact that plots of the community were taken in sites far from the edge effect and sloping areas. Species found on strong slopes are less disturbed and would be rich in species composition (Tilahun et al 2011;Gebrehiwot et al 2019).…”
Section: Floristic Composition and Diversitymentioning
confidence: 99%
“…Patterns of species community is associated with environmental factors such as climate, topography, and soil as well as anthropogenic and livestock disturbances (Whittaker et al 2003). Ecological study conducted in Ethiopia by Woldu et al (1989), Friis (1992), Bekele (1994), Aynekulu (2011), Kelbessa and Girma (2011) and Gebrehiwot et al (2019) reported importance of environmental variables (altitude, slope, landscape, disturbances, and soil physical and chemical properties) in separation of forest communities.…”
Section: Plant Community and Environmental Variables Relationship (Ormentioning
confidence: 99%
“…Soils having high organic matter and moisture holding capacity of the silt loam of soil are suitable for species growth and diversity (Brown 2003;O'Geen 2006). Furtherly, species found in strong slope are less disturbed and would be rich in species composition (Tilahun et al 2011;Gebrehiwot et al, 2019). The longest arrow of altitude in the ordination axis was positively correlated with community type four (Euclea racemosa -Acacia abyssinica) than the other community types.…”
Section: Plant Community and Environmental Variables Relationship (Ormentioning
confidence: 99%
“…Many ecological studies reveal two main patterns of relationships between species richness and altitude: a monotonic decline in species richness with increasing elevation, and a hump-shaped relationship, with mid-elevation peaks in species richness [ 1 ]. Both models are well documented by studies focused on plants and vertebrates, especially birds and mammals [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Recent studies show that the second pattern seems to be more common [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%